Synthesis, structure, and H-2/CO2 adsorption in a three-dimensional 4-connected triorganotin coordination polymer with a sqc topology - Chandrasekhar, Vadapalli; Mohapatra, Chandrajeet; Banerjee, Rahul; Mallick, Arijit (Inorganic Chemistry, 2013)
A 4-connected triorganotin 3D coordination polymer in a sqc topology has been shown to possess 1D microchannels along its crystallographic a axis. This main-group-element-containing framework structure shows selective gas adsorption, preferring CO2 and H-2 over N-2.